2008
DOI: 10.1016/j.annepidem.2008.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Lifecourse Social Conditions and Racial Disparities in Incidence of First Stroke

Abstract: Purpose-Some prior studies found excess stroke rates among blacks persisted after adjustment for socioeconomic status (SES), fueling speculation regarding racially patterned genetic predispositions to stroke. Prior research was hampered by incomplete SES assessments, without measures of childhood conditions or adult wealth. We assess the role of lifecourse SES in explaining stroke risk and stroke disparities.Methods-Health and Retirement Study participants age 50+ (n=20,661) were followed on average 9.9 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 59 publications
1
77
1
Order By: Relevance
“…In contrast to a previous study from our group that focused on dental health and particularly periodontitis as a stroke risk factor and that guided several hypotheses for the present work [22], paternal profession was not an independent risk factor of stroke here. In other studies, childhood socioeconomic conditions predicted stroke risk independently of social status in adulthood [18,21]. Professional training was the one social factor that was most strongly associated with stroke risk, although behavioral and other risk factors clearly influenced its predictive value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to a previous study from our group that focused on dental health and particularly periodontitis as a stroke risk factor and that guided several hypotheses for the present work [22], paternal profession was not an independent risk factor of stroke here. In other studies, childhood socioeconomic conditions predicted stroke risk independently of social status in adulthood [18,21]. Professional training was the one social factor that was most strongly associated with stroke risk, although behavioral and other risk factors clearly influenced its predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in disease risk may be partly determined by cumulative differential exposure to adverse material conditions and behavioral and psychosocial risks during an individual’s lifetime [21]. We adopted a life course perspective and assessed indicators of social status during various periods of life.…”
Section: Discussionmentioning
confidence: 99%
“…20,27 In a US national longitudinal study, adjustment for both childhood and adult social conditions explained nearly all the association between ethnicity and stroke incidence. 28 A study reported that 14% to 64% of the increased stroke mortality in black men was explained by socioeconomic factors but with no significant association in black women. 27 Studies on mortality differences between blacks and whites have however been inconsistent with some studies reporting an increased mortality and others demonstrating a survival advantage in blacks.…”
Section: Ethnic Differencesmentioning
confidence: 99%
“…This approach provides a framework to establish priorities in service and research areas. 39 There are many possible explanations for why racial-ethnic disparities exist, including cultural variations in perceptions of health and the healthcare system, environmental exposures, genetic factors, 40 SES, 41 disadvantage in early childhood, 42 fear, mistrust, prejudice, 39 and educational level. 43 The goal of Healthy People 2010 was to eliminate these disparities.…”
Section: Definitionsmentioning
confidence: 99%